2010
DOI: 10.1111/j.1365-294x.2010.04875.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of introduction and adaptation during the invasion of Aegilops triuncialis (Poaceae) into Californian serpentine soils

Abstract: Multiple introductions can play a prominent role in explaining the success of biological invasions. One often cited mechanism is that multiple introductions of invasive species prevent genetic bottlenecks by parallel introductions of several distinct genotypes that, in turn, provide heritable variation necessary for local adaptation. Here, we show that the invasion of Aegilops triuncialis into California, USA, involved multiple introductions that may have facilitated invasion into serpentine habitats. Using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 45 publications
3
47
0
Order By: Relevance
“…Although transgenerational plasticity effects cannot be ruled out completely, the fact that edge source maternal plants produced consistently larger seeds across all planting conditions argues for a least some genetic contribution to this phenotypic variation in seed size. The likelihood that phenotypic differences between serpentine and non-serpentine populations of A. triuncialis have some genetic basis is also supported by previous common garden glasshouse experiments (Lyons et al 2010;Meimberg et al 2010). These glasshouse studies found significant variation between serpentine and non-serpentine populations in a number of phenological and morphological traits.…”
Section: Discussionsupporting
confidence: 65%
“…Although transgenerational plasticity effects cannot be ruled out completely, the fact that edge source maternal plants produced consistently larger seeds across all planting conditions argues for a least some genetic contribution to this phenotypic variation in seed size. The likelihood that phenotypic differences between serpentine and non-serpentine populations of A. triuncialis have some genetic basis is also supported by previous common garden glasshouse experiments (Lyons et al 2010;Meimberg et al 2010). These glasshouse studies found significant variation between serpentine and non-serpentine populations in a number of phenological and morphological traits.…”
Section: Discussionsupporting
confidence: 65%
“…Meimberg et al (2010) sampled invasive populations throughout California and identified three lineages (East, West and South) with the East and West lineages occupying much larger areas than the South (Meimberg et al 2010). To minimize maternal effects, we used offspring from a common garden experiment (Espeland and Rice 2012), which included 11 populations (8 East and 3 West, defined as populations 102, 103, 105, 106, 107, 115, 117, 119, 122, 124 and 125 in Meimberg et al 2010).…”
Section: Species Selection and Seed Sourcementioning
confidence: 99%
“…To minimize maternal effects, we used offspring from a common garden experiment (Espeland and Rice 2012), which included 11 populations (8 East and 3 West, defined as populations 102, 103, 105, 106, 107, 115, 117, 119, 122, 124 and 125 in Meimberg et al 2010). Populations sampled in Meimberg et al (2010) lacked within population variation, and nearby populations were usually of the same lineage. ''West'' populations were found in the western part of northern California, specifically Mendocino, Colusa, Napa, Solano, and Yolo Counties.…”
Section: Species Selection and Seed Sourcementioning
confidence: 99%
See 2 more Smart Citations